IMPLEMENTASI KONSEP RUHUL JIHAD DALAM PROFESI KEGURUAN (Studi Kasus di IDIA Puteri PP. Al-Amien Prenduan) - Fitri Dewi Oktavia; Musleh Wahid; Ida Riyani (PAI RAFAH, 2021)
Jihad has a very broad scope of meaning, in this context what is meant by jihad is in the sense of educating and teaching knowledge to fight ignorance and moral decay. In order to fight ignorance and moral decay, a teacher must meet the standards of professional competence and have the spirit of jihad in him. This study aims to describe a case study of the implementation of the concept of the spirit of jihad in the teaching profession. The forms of the spirit of jihad in a teacher can be seen from the nature and personality of a teacher such as sincere, patient personality and unyielding nature as well as optimism in carrying out all orders and obligations. The research method used a qualitative approach and data collection was carried out using interview and observation techniques, while the data were analyzed using Milles and Huberman's data analysis theory and checking the validity of the data using triangulation techniques.The spirit of jihad from the perspective of IDIA teachers is to mobilize all their potential to teach the knowledge they have by hoping for Allah's blessing without expecting material rewards. This is implemented in the form of sincerity in carrying out their duties, discipline in all things, patient in dealing with and responding to students, being serious in all things, praying for students and evaluating well and being able to take advantage of the results of student evaluations to develop lesson plans. which is even better according to the level of ability of students and the character of students.